The Future Of The Arabic Language - Muhammad Bachtiar Syamsuddin (Ijaz Arabi Journal of Arabic Learning, 2022)
The purpose of this research is to follow these people who are interested in Arabic in Indonesia and want Arabic to be a second language in Indonesia, and so the updated comprehensive station to reach this purpose is the bases of the desired cultural renaissance on a factual scientific, and critical vision of local, regional and global levels, with the need to adjust to the age and other opinions. Especially the future of the Islamic world, such as Indonesia. The method used in this research was library research. The data were collected, quoted, adapted, and analyzed using a content analysis approach toward the representative and relevant literature before finally being discussed and concluded. The results expected from this research were; 1). Arabic is distinguished from other languages as it is not only a means of communication but also a soul and official language among Muslims. All the fundamental main reference books of Tauhid and Syariah, which refer to Al Qur’an and As-Sunnah, were written in Arabic, 2). Arabic has been a language of thought, and a global science in medieval, which in many ways has passed European movement and development were, with its sophisticated features, it managed to be the answer to every developmental need of humans, 3). The Arabian people's economic, social, and cultural modern roles have boldened the internationalization of the Arabic language, which has been one of the official languages in the UN, which has affected more interest in learning it.